Practice of CrossRef extensible markup language coding and more advanced information for CrossRef deposits - Rachael Lammey (Science Editing, 2014)
CrossRef is an association of scholarly publishers that develops shared infrastructure to support more effective scholarly communications. This infrastructure is centred around the Digital Object Identifier (DOI), and the associated bibliographic metadata that publishers deposit with CrossRef. To deposit this metadata, publishers need to provide the relevant information to CrossRef in extensible markup language (XML). Some publishers have a high level of XML expertise, and some are less familiar with formatting XML and need more assistance in order to register DOIs with CrossRef. There are some basics of depositing which can be picked up quickly, with the help of CrossRef tools, but there is a lot of information that publishers can provide via their XML to supplement the basic deposit information. This article will cover some of the more advanced information that publishers can deposit with CrossRef when they register DOIs, to help them participate in additional CrossRef services and provide additional value for the scholarly research community.